Culture-Specific Items in The Musical Theater Script “Linie 1: Das 7. Bild” By Volker Ludwig: Case Study in The “Kultur Und Übersetzung” ClassNest - Finalia, Cicu; Ekawati , Dian (Future Science)
As in linguistics or pragmatics, translation research requires suitable means to define and to analyze culture-specific items. However, it is not always easy to find these analytical means. This challenge arises because in language all elements are in fact culturally produced, starting with the language itself. Thus, exploring the culture-specific items in a translation work also involves examining the language used in the work. This study presents an overview of the phenomenon of translating culture-specific items in musical theater script from German into Indonesian by students of German Department of Cultural Sciences Faculty Universitas Padjadjaran in the class “Kultur und Übersetzung'' in the summer semester of 2021 (February – July 2021). Using a qualitative case study method on the musical theater script “Linie 1: Das siebte Bild'' by Volker Ludwig (1985) and its Indonesian translation, the universal culture-specific items according Kluckhohn (1953) that emerged in the musical theater script, namely language, knowledge system, technology and facility systems, arts, living systems, religious systems, social systems, and community organizations are analyzed. The culture-specific items identified by students were further interpreted using the theory of Aixelá (1996). The findings of this study indicate that the culture-specific items identified by the students in the source text are embodied in the text and they translate the elements with conservation strategy. The question of how far the results of the analysis can be generalized to a particular culture and whether the aesthetic elements of the text also play an important role in the translation process will be discussed further.